Composts from green sources show an increased suppressiveness to soilborne plant pathogenic fungi: Relationships between physicochemical properties, disease suppression, and the microbiome. (October 2019) - De Corato, Ugo; Patruno, Luigi; Avella, Nicola; Lacolla, Giovanni; Cucci, Giovanna
Abstract: The need for studying tailored composts, as new feedstocks become available with time, increases the in-depth studies of suppressive composts derived from green sources and agro-wastes recycling. The composition, diversity and variability of microbiomes within a collection of 10 composts were investigated by amplicon sequencing and bioinformatics analyses. The observed differences in microbiome structure were related to the different compost origin. The multi-suppressive properties of composts from agricultural residues, agro-industrial co/by-products, and plant green-waste showed the most complex microbiome structure, which included either biocontrol agents associated with the control of Rhizoctonia damping-off in bean and Verticillium wilt in eggplant or microbial consortia for controlling Pythium damping-off in cucumber and zucchini and Phytophthora root rot in tomato and azalea. In contrast, the pathogen-specific property of composts from municipal solid waste and co-composted cow manure household waste showed a microbiome that overall included biocontrol agents against Fusarium wilt in tomato, melon and basil. The highest correlations between physicochemical properties, disease suppression, and the microbiome have allowed to make a helpful matrix to know how relationships among these variables of composts could be established and quantified for predicting their suppressive properties basing on the physicochemical properties and the microbiome. Highlights: A collection of compost from green sources was screened for plant disease suppression. Compost microbiome plays the significant role in controlling soil-borne pathogens. Amplicon sequencing and bioinformatics analyses were used for microbiome analyses. Compost physicochemical properties, suppression and the microbiome were correlated.